AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) DAN DAUN ANGSANA (Pterocarpus indicus Wild.) PADA MENCIT JANTAN GALUR BALB/C - Yance Anas; Devi Nisa Hidayati; Aristya Kurniasih; Lalu Ksatria D.S. (Universitas Wahid Hasyim Semarang, 2016)
ABSTRACT Traditionally, jackfruit leaves (Artocarpus heterophyllus Lam.) and angsana leaves (Pterocarpus indicus Wild.) have been used as an herb for diarrhea treatment. The purpose of this experimental study was to investigate the antidiarrheal effect of jackfruit leaves ethanol extract (JLEE) and angsana leaves ethanol extract (ALEE) on Balb/C male mice with castor oil-induced diarrhea method. The study design is a randomized matched two group post test-only. JLEE and ALEE produced by maceration. An antidiarrheal activity of both of extracts compared with loperamide-HCl 10 mg/Kg BW. JLEE (100, 200 and 400) mg/Kg BW and ALEE (80, 160 and 320) mg/Kg BW significantly (p <0.05) decrease the amount of liquid and soft feces, and delay the onset of diarrhea compared with controls (NaCl 0.9% 10 mL/Kg BW). The ability JLEE 400 mg/Kg BW and EEDA 320 mg/Kg BW on inhibiting the formation liquid and soft feces are higher than loperamide HCl 10 mg/Kg BW with antidiarrheal effect amounted to 72.31%, 65.47%, and 54.46% respectively. The potency of JLEE and ALEE as antidiarrheal (ED50) are (20.85 and 3.52) mg/Kg BW respectively. However, in this study, a single dose of loperamide-HCl, JLEE and ALEE treatments are not able to heal the diarrhea symptom (p> 0.05). Keywords: Antidiarrheal, castor oil-induced diarrhea,ethanol extract, Artocarpus heterophyllus Lam., Pterocarpus indicus Wild.